PERLINDUNGAN ANAK TERLANTAR MENURUT HUKUM ISLAM - Sulaiman Tamba (Universitas Islam Sumatera Utara, 2019)
AbstractChild protection in Islam is known as Hadhanah. Hadhanah is a child care by parents. In general, children are related to the biological relationship between man and woman. This research applies descriptive method through normative approach (legal research), which is based on the facts in the field that are questionable, carried out by examining various aspects in terms of applicable laws and regulations. A neglected child is not regarded only as a poor one begging under the red lights. But, the neglected children also include children whose needs are not fulfilled as stipulated in the law. Child care is ultimately the responsibility of both parents. The care in this case contains a variety of problems relating to the needs of children, whether it is economic problems, education, the right to life and everything that becomes a child's basic needs, with both parents are still in one family or divorced. From the needs of children which are not fulfilled and other factors, neglected children are ones whose basic needs are not fulfilled. Keywords: Legal Protection, Child, Neglected